Microplastics in soil induce a new microbial habitat, with consequences for bulk soil microbiomes - Kublik, Susanne; Gschwendtner, Silvia; Magritsch, Tobias; Radl, Viviane; Rillig, Matthias C.; Schloter, Michael (Frontiers in Environmental Science, 2022)
Microplastic (MP) pollution poses a threat to agricultural soils and may induce a significant loss of the soil quality and services provided by these ecosystems. Studies in marine environments suggest that this impact is mediated by shifts in the microbiome. However, studies on the mode of action of MP materials on the soil microbiome are rare, particularly when comparing the effects of different MP materials. In this study, we characterized the microbiota colonizing two different MP materials, granules made of polypropylene (PP) and expanded polystyrene (ePS), introduced into arable soil and incubated for eight weeks using a molecular barcoding approach. We further assessed the consequences on the microbiome of bulk soil. The complexity of the bacterial communities colonizing MP materials was significantly higher on ePS compared to PP. Many of the detected genera colonizing the MP materials belonged to taxa, that are known to degrade polymeric substances, including TM7a, Phenylobacterium, Nocardia, Arthrobacter and Streptomyces. Interestingly, in bulk soil samples amended with MP materials, microbial diversity was higher after eight weeks compared to the control soil, which was incubated without MP materials. The composition of bacterial communities colonizing the MP materials and bulk soil differed. Mainly Acidobacteria were mostly found in bulk soil, whereas they were rare colonizers of the MP materials. Differences in diversity and community composition between the MP affected bulk soil samples were not found. Overall, our data indicate that MP materials form a new niche for microbes in soil, with a specific community composition depending on the materials used, strongly influencing the bulk soil microbiota in the short term. Long-term consequences for the soil microbiome and associated functions including different soils need to be further elaborated in the future for a proper risk assessment of the mode of action of MP materials in terrestrial ecosystems.